The Impact of Self-Acceptance and Emotional Regulation on the Experience of Empty Nest Syndrome in the Older Adult - Salsabila, Alfida; Uyun, Muhamad (Jurnal Sains Psikologi, 2024)
One of the crisis phases in families entering the middle age phase is the feeling of losing their role in raising children and feeling empty because the children no longer live in the same house. This term is known as empty nest syndrome. Self-acceptance and emotional regulation play an essential role in the impact of empty nest syndrome experienced by older adults. This research aims to prove the further impact of self-acceptance and emotional regulation on the experience of empty nest syndrome in older adults. The self-acceptance scale, emotional regulation scale, and empty nest syndrome scale were adapted by the author. The research respondents were 30 older people at the Siti Anna Bangka Belitung Retirement Home. The sampling technique uses purposive sampling. From the results of multiple linear regression analysis, it is known that self-acceptance and emotional regulation are related to empty nest syndrome, and simultaneously, self-acceptance, emotional regulation, and empty nest syndrome are significantly associated with each other.